Differential hierarchical metabolites expression of red/white Salacca sumatrana arillus and its molecular docking studies - Miftahul Huda Fendiyanto; Rizky Dwi Satrio; I Dewa Ketut Kerta Widana; Mentari Putri Pratami; Isna Arofatun Nikmah; Didi Darmadi (Society for Indonesian Biodiversity, 2021)
Abstract. Fendiyanto MH, Satrio RD, Widana IDKK, Pratami MP, Nikmah IA, Darmadi D. 2021. Differential hierarchical metabolites expression of red/white Salacca sumatrana Arillus and its molecular docking studies. Biodiversitas 22: 1014-1024. Salak Sidempuan (Salacca sumatrana) is one of the medicinal plants originating from tropical countries. However, there is very little research on the study of finding bioactive compounds in S. sumatrana using the metabolomic approach. Here, we use two population types of S. sumatrana, e.g., fruit with red and white arillus. We extracted the compounds from the two tissues using the GC-MS technique and further analyzed their antiviral potential using an in-silico molecular docking technique. Fold change analysis showed that in white arillus there were 21 upregulated compounds and 25 downregulated compounds. Metabolites that have high expression in white arillus tissue are ranxinic acid, nicotinic alcohol, stearic acid, 2-furan carboxaldehyde, and others. Six accessions from S. sumatrana based on PCA analysis and separate dendrogram according to the type of arillus, i.e., red and white arillus. Two compounds that act as antivirals found in this study are stearic acid and palmitic acid based on preliminary molecular docking studies. These two compounds could be used for further studies as a preventive measure against SARS-Cov-2 in the future, however, it needs further comprehensive and clinical analysis the future. In conclusion, metabolites in white arillus were distinctly different from red arillus of Snake fruits. In addition, studies on differential metabolite expression on two types of arillus (red/white) can be used as markers in identifying arillus color early by plant breeders.